Twice Deployment Node Balance Algorithm for Road Network Surveillance. (25th May 2014) - Chen, Liangyin; Li, Yecheng; Li, Zhanghua; Li, Wenke; Su, Panlan; Cheng, Hua; Luo, Qian; Yin, Feng; Jiang, Yushi
Abstract : This paper proposes a twice deployment node balance algorithm (TDNB) which guarantees successful detection of the moving target on road networks. Through dividing the deployment of the sensor nodes into two phases instead of deploying all the sensors at one time, TDNB has a better performance. In the former phase, some of the sensors are deployed on the road at random. In the latter phase, the rest of the sensors are deployed on demand to make the number on each path the same. Due to the equivalence of the node's number, the network will have a prolonged lifetime after inserting nodes into the segment according to this algorithm. TDNB extends the network's lifetime remarkably compared with the former algorithms. Furthermore, TDNB enables us to insert nodes to the segment required in the network instead of all the segments, which reduces the workload to a large extent. In short, without increasing the number of sensors in road network, TDNB has a better performance compared to VISA in terms of network lifetime, which meets the demand for persistent monitoring application.